Bilateral supplemental permanent maxillary lateral incisors in a non-syndromic patient - Bhullar, Mandeep Kaur (BMJ Publishing Group, 2014)
A supernumerary tooth is an additional entity to the normal series and can be seen in all quadrants of the jaw. Occurrence may be single or multiple, unilateral or bilateral, erupted or impacted in one or in both jaws. Multiple supernumeraries are rare in individuals with no other associated disease or syndromes. The conditions commonly associated with an increased prevalence of supernumerary teeth include cleft lip and palate, cleidocranial dysplasia and Gardner syndrome. The supplemental supernumerary refers to a duplication of teeth in normal series and is found at the end of a tooth series. A supplemental tooth may closely resemble the teeth of the group to which it belongs or it may bear little resemblance in size or shape to the teeth with which it is associated. This report presents a case with bilateral supplemental upper permanent lateral incisors without any symptoms of associated disorders.